2021
DOI: 10.1002/anie.202104410
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Syntheses of 8,9‐Seco‐ent‐kaurane Diterpenoids Enabled by an Electrochemical ODI‐[5+2] Cascade

Abstract: An electrochemical ODI‐[5+2] cascade reaction was developed which enables the rapid assembly of diversely functionalized bicyclo[3.2.1]octadienones from sensitive ethynylphenols. By combining a directed retro‐aldol/aldol process, a [2,3]‐sigmatropic rearrangement, and an Al(O‐iPr)3‐promoted reductive 1,3‐transposition, the asymmetric total syntheses of five 8,9‐seco‐ent‐kauranoids—(−)‐shikoccin, (−)‐O‐methylshikoccin, (−)‐epoxyshikoccin, (+)‐O‐methylepoxyshikoccin, and (+)‐rabdo‐hakusin—have been achieved in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Zuschriften 15020 www.angewandte.de premature reduction of the fragile peroxide anion by the existing selenide, producing enone 8 in 51 % yield over two steps. At this point, the exo-D 16,17 -double bond needed to be masked prior to modification of the more inert D 11,12 -alkene. In this regard, 8 was converted to a thioether (3.7:1 dr at C16), which, on treatment with mCPBA to trigger both [2,3]sigmatropic rearrangement and sulfone formation, provided 29 in 64 % yield.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 3 more Smart Citations
“…Zuschriften 15020 www.angewandte.de premature reduction of the fragile peroxide anion by the existing selenide, producing enone 8 in 51 % yield over two steps. At this point, the exo-D 16,17 -double bond needed to be masked prior to modification of the more inert D 11,12 -alkene. In this regard, 8 was converted to a thioether (3.7:1 dr at C16), which, on treatment with mCPBA to trigger both [2,3]sigmatropic rearrangement and sulfone formation, provided 29 in 64 % yield.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Catalytic hydrogenation of the D 11,12 -alkene was realized in the presence of Pd/C and H 2 (400 psi). Direct subjection of the resulting mixture to pTsOH•H 2 O at room temperature for 30 min to release the exo-D 16,17 -alkene furnished (À)-shikoccidin (7) in 87 % yield. On the other hand, by performing the reaction at 35 8C for 3 h to facilitate an additional retro-aldol/ elimination process, (À)-shikoccin (2) was obtained exclusively in 80 % yield.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have described a novel and efficient oxidative dearomatization-induced (ODI) [5+2] cycloaddition/pinacol rearrangement cascade reaction with the aid of a hypervalent iodine­(III) reagent, which offers a robust synthetic protocol for the assembly of bicyclo[3.2.1]­octane frameworks from readily available vinylphenols (Scheme c) . Subsequently, substantial progress in tetracyclic diterpenoid syntheses via ODI-[5+2] cascade reaction has been achieved through our persistent efforts in the past few years. , Nevertheless, during the adventures, we found that the non-negligible drawbacks associated with the strongly acidic byproducts derived from the hypervalent iodine reagents greatly limited functional group tolerance, especially for the acid sensitive benzyl alcohol-containing substrates due to the tendency to generate an unstable quinonmethide intermediate. , Therefore, further improvements remain urgently needed in terms of the compatibility between diverse functional groups and the established conditions for the ODI-[5+2] cascade reactions.…”
mentioning
confidence: 99%